2023
DOI: 10.3389/fmed.2022.1017000
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative prognostic nutritional index with risk of postoperative delirium: A systematic review and meta-analysis

Abstract: Study objectiveTo assess the association between prognostic nutritional index (PNI) and risk of postoperative delirium (POD) in adult patients.MethodsMEDLINE, Google scholar, EMBASE, and Cochrane library databases were searched from inception till April 2022. The primary outcome was the association between PNI and the risk of POD, while the secondary outcomes were correlations of other prognostic factors with POD risk. The correlation between PNI and the incidence of POD was assessed with three approaches: Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In this article, we used the PNI index to assess the nutritional status of patients at the time of onset, after radiotherapy, and in the late stage of the disease. The PNI, compared to previous single nutritional indicators, uses serum protein levels and has greater prognostic value for patients with glioma, which has been veri ed by several studies 14 . In the late stage of the disease, the overall PNI of patients is the lowest among the three time periods, and it is linearly related to the PNI after radiotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…In this article, we used the PNI index to assess the nutritional status of patients at the time of onset, after radiotherapy, and in the late stage of the disease. The PNI, compared to previous single nutritional indicators, uses serum protein levels and has greater prognostic value for patients with glioma, which has been veri ed by several studies 14 . In the late stage of the disease, the overall PNI of patients is the lowest among the three time periods, and it is linearly related to the PNI after radiotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…However, our findings regarding the negative association between obesity and delirium risk are quite intriguing. Though obesity is a well-known risk factor for chronic cognitive impairment [16], mixed results have been reported about the association of BMI with delirium [17,18]. Existing research involving postoperative delirium [19] or intensive care unit delirium [20,21] as an outcome variable found that having a high BMI was a protective factor for delirium.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis investigating the association between preoperative PNI and the incidence of POD in adult patients receiving surgery under general anesthesia demonstrated that a lower PNI was correlated with a higher risk of POD [82].…”
Section: Postoperative Complicationsmentioning
confidence: 99%